Molecular Characterization and Pathogenesis of Newcastle Disease Virus Isolated from Brontok Eagle in West Java, Indonesia - Angeliya, Liza; Kristianingrum, Yuli Purwandari; Asmara, Widya; Wibowo, Michael Haryadi (HAYATI Journal of Biosciences, 2022)
Newcastle disease (ND) is a contagious disease in poultry and numerous birds of various ages. Eagle is considered a potential reservoir for ND transmission as a wild  bird. This  research  was  conducted  to  molecularly  characterize  Newcastle disease virus (NDV) isolated from ND cases in Brontok Eagle and analyze the pathogenesis  in  chicken  embryos.  qRT-PCR  was  conducted  as  conﬁrmation of  NDV  without  mixing  Avian  Inﬂuenza  (AI).  Sequencing  the  fusion  (F)  and haemagglutinin-neuraminidase (HN) genes from the three NDVs was performed with  a  speciﬁc  primer. Amino  acid  sequence  compared  with  other  NDV  from Genbank.  Pathogenicity,  genetic  variation,  distance,  and  phylogenetic  studies were  analyzed  using  bioinformatics  software  (MEGA-X).  This  study  analyzed pathogenesis  based  on  lesions  and  distribution  of  viral  antigens  in  chicken embryos  infected  with  NDV.  Observations  were  based  on  tissue  lesions  with HE and IHC staining. NDV isolated from three Brontok Eagles is classiﬁed as velogenic  strain,  virulent  NDV  (KRQKRF),  and  belonging  to  Genotype  VII subgenotype VII.2. The NDV was detected in various organ lesions, more severe in  the  pulmo,  trachea,  proventriculus,  and  intestine  of  chicken  embryos. That is still similar to the previous case reports in the ﬁeld. These results show that NDV, which infected Brontok Eagle, has similar molecular characteristics and pathogenesis in chickens. These cases could be a threat to the poultry industry. Further research, surveillance, and monitoring of wild birds are needed to obtain more NDV epidemiological information in wild birds.